2010
DOI: 10.1029/2010gl042811
|View full text |Cite
|
Sign up to set email alerts
|

Superposed epoch study of PV5/3 during substorms, pseudobreakups and convection bays

Abstract: We present a superposed epoch study to examine the entropy parameter PV5/3, for isolated substorms, pseudobreakups and convection bays observed by Geotail in the near‐Earth plasma sheet, by using a flux‐tube‐volume formula with coefficients adjusted to fit magnetic field models for a variety of conditions. It is found that the changes of PV5/3 for these three types of events are distinct: (1) for substorms, PV5/3 increases continuously during the growth phase, decreases after dipolarization, and maintains a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…Therefore, the manifestation in this case is that the magnetic field strength is larger than empirical models in the near-Earth plasma sheet and plasma pressure is well enhanced near geosynchronous orbit. There is neither largescale explosive reconfiguration nor strong injections of unambiguous bubbles in SMCs [Yang et al, 2010], though weak and short-lived injections have been observed near geosynchronous orbit [Sergeev et al, 2001]. To our knowledge, at least two scenarios are related to the formation of low PV 5/3 boundary used in our simulation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, the manifestation in this case is that the magnetic field strength is larger than empirical models in the near-Earth plasma sheet and plasma pressure is well enhanced near geosynchronous orbit. There is neither largescale explosive reconfiguration nor strong injections of unambiguous bubbles in SMCs [Yang et al, 2010], though weak and short-lived injections have been observed near geosynchronous orbit [Sergeev et al, 2001]. To our knowledge, at least two scenarios are related to the formation of low PV 5/3 boundary used in our simulation.…”
Section: Discussionmentioning
confidence: 98%
“…The coefficient one half in front of the SMC term in equation (1) represents the degree of the depletion on the boundary in the SMC run compared with the substorm growth phase [Yang et al, 2010]. Therefore, PV 5/3 = 2/3 P s h s l s on the boundary in SMC is set to about one half of that in the growth phase run.…”
Section: Rcm-e Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Dipolarization events consist of a rapid change from stretched tail-like to more dipolar magnetic fields and are identified most commonly to be the rapid increase of B z within the central plasma sheet. Magnetic field lines threading through the region of enhanced B z are characterized by reduced field line entropy [e.g., Wolf et al, 2009;Birn et al, 2009;Yang et al, 2010;Kim et al, 2010;Dubyagin et al, 2011] and commonly denoted as "bubble" [Pontius and Wolf , 1990] or "dipolarizing flux bundle" (DFB) [Liu et al, 2013a[Liu et al, , 2013b. Earthward moving short dipolarization pulses are typically associated with an earthward flow burst [e.g., Nakamura et al, 2002;Runov et al, 2009;Sergeev et al, 2009], whereas an increase of B z toward a more persistent higher level may be observed closer to Earth without significant flow .…”
Section: Introductionmentioning
confidence: 99%